336 Effect of Lemborexant Versus Placebo and Zolpidem on REM Sleep by Quarter Night Intervals in Older Adults with Insomnia Disorder. (3rd May 2021) - Zammit, Gary; Roth, Thomas; Kumar, Dinesh; Perdomo, Carlos; Atkins, Norman; Moline, Margaret
Abstract: Introduction: Effects of the dual orexin receptor antagonist lemborexant (LEM) on sleep architecture in adults ≥55y with insomnia disorder were assessed in Study E2006-G000-304 (Study 304; SUNRISE-1; NCT02783729). These post hoc analyses of Study 304 examined the acute effect of LEM on REM pressure (REM latency [REM-L] and REM by quarter of the night [QoN]). Methods: This study was a 1mo, randomized, double-blind, placebo- and active-controlled (zolpidem tartrate extended-release 6.25mg [ZOL]) study of LEM (5mg, LEM5; 10mg, LEM10). Subjects received placebo (n=208), ZOL (n=263), LEM5 (n=266), or LEM10 (n=269). Two nights of PSGs were recorded at baseline, first 2 (N1/2), and last 2 (N29/30) treatment nights. Results: Baseline REM-L (minutes) was similar across treatments (98.4–101.4). Significant decreases from baseline in REM-L were observed for LEM5 (−42.6 [53.9]) and LEM10 (−49.6[52.9]) vs placebo (−6.9[54.5]) and ZOL (0.2[54.2]) on N1/2 (all P<0.0001). No difference was observed for ZOL vs placebo. Baseline REM (minutes) for each QoN was similar across treatments. In Q1, mean(SD) REM (minutes) on N1/2 was 16.5(9.7), 19.7(10.5), 10.3(8.2), and 8.5(7.6) for LEM5, LEM10, placebo, and ZOL, respectively. The difference was significant for LEM5 and LEM10 vs placebo and ZOL (all P<0.0001), and ZOL vs placebo (P<0.05). In Q2, mean(SD) REM on N1/2 was 19.2(9.4), 21.6(10.0), 17.9(8.9), and 17.2(9.3) for LEM5, LEM10, placebo, and ZOL, respectively. The difference was significant for LEM10 vs placebo (P<0.0001) and for LEM5 and LEM10 vs ZOL (P<0.01, P<0.0001, respectively). No difference was observed for ZOL vs placebo. In Q3, mean(SD) REM on N1/2 was 23.3(10.3), 25.9(9.7), 20.8(9.4), and 22.8(9.9) for LEM5, LEM10, placebo, and ZOL, respectively. The difference was significant for LEM5, LEM10, and ZOL vs placebo (P<0.01, P<0.0001, P<0.05, respectively) and LEM10 vs ZOL (P<0.001). In Q4, mean (SD) REM on N1/2 was 23.8(9.4), 26.1(11.0), 21.6(10.9), and 22.5(10.1) for LEM5, LEM10, placebo, and ZOL, respectively. The differences were significant for LEM5 and LEM10 vs placebo (P<0.05, P<0.0001, respectively), and for LEM10 vs ZOL (P<0.0001). Generally, similar findings were noted at N29/30; these data will be reported. Conclusion: LEM, but not ZOL, acutely increases REM pressure as evidenced by REM latency and REM duration per quarter. Support (if any): Eisai Inc.